MICROBIAL AND PHYSICO-CHEMICAL ASSESSMENT OF SOIL AND WATER AROUND WASTE DUMP SITES - Hilda Emmanuel-Akerele; Favour Peter (International Journal of Applied Biology, 2021)
In Nigeria, the reliance on sanitary landfills is a common phenomenon in the disposal of waste materials. The aim of the study was to ascertain the physicochemical and microbiological effect landfill has on its surrounding soil and water. Four water samples and five soil samples were collected each from Ile-Epo and Legacy dumpsites and the adjoining areas. Physicochemical parameters determined were temperature, pH, total dissolved solids (TDS), total hardness (TH), and electrical conductivity. Most of these parameters indicated pollution but were below the World Health Organization (WHO) limits for consumption in the water. Microbiological analysis was carried out using standard microbiological procedures. The mean bacteria count and fungal count for water and soil samples are 26.41 CFU/mL and 10.00 CFU/mL; and 26.30 and 14.50 (CFU/G) respectively. The antibiotic susceptibility pattern of the bacterial isolates against conventional antibiotics displayed varying degree of susceptibility and resistance; the bacterial contaminants were susceptible to Augmentin, Gentamycin and Chloramphenicol and resistant to Pefloxacin, Amoxacilin, Tarivid, Streptomycin, Sparfloxacin and Ciprofloxacin. The results obtained in this study showed that the leachate generated from the landfill site has a minimal impact on the groundwater and soil quality in the locality.